Providing Employers with Incentives to Train Low-Skilled Workers: Evidence from the UK Employer Training Pilots - Abramovsky, Laura; Battistin, Erich; Fitzsimons, Emla; Goodman, Alissa; Simpson, Helen (Journal of Labor Economics, 2011)
We use unique workplace and employee-level data to evaluate a major UK government pilot program to increase qualification-based, employer-provided training for low-qualified employees. We evaluate the program’s effect using a difference-in-differences approach. Using data on eligible employers and workers we find noevidence of a statistically significant effect on the take-up of training in the first 3 years of the program. Our results suggest that the program involved a high level of deadweight and that improving the additionality of the subsequent national program is crucial if it is to make a significant contribution toward government targets to increase qualification levels.